Strategia w ujęciu dynamicznym - Krupski, Rafał (The Strategy in a Dynamic Perspective, 2008)
The article presents three conceptions of the strategy in a dynamic perspective. The first conception derives from scenario methods in both classical perspective and the perspective of strategic options. The second conception presents the strategy as the long-term schedule of new products introduction. The third conception is the author's own conception and presents the strategy as the peculiar sequence of strategic decisions. This sequence concerns products, markets, the sources of capital raising, organizational-legislative companies forms and strategic alliances. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 93-101